Orientasi Politik Pemilih Perempuan pada Pemilu Tahun 2019 di Kabupaten Kepulauan Seribu Provinsi DKI Jakarta - Ikatrina Rosyidah; Sri Budi Eko Wardani (Syntax Corporation Indonesia, 2024)
The purpose of this study is to explain the extent of the influence of socioeconomic status and political participation on the political orientation of women voters in the 2019 General Election in the Thousand Islands Regency, DKI Jakarta Province. The method used in this study is a quantitative approach, namely with one of the characteristics commonly found in quantitative research with causality, which tries to explain the question